Design And Development of Tripod Hopping Robot - Anuar , Mohamed Kassim; Nurul Hafizah , Abdul Rahim; Takashi, Yasuno (2012)
In this paper, we discuss on the validity of using infrared ranging sensor instead of using ultrasonic ranging sensor for the developed tripod hopping robot. The infrared sensor is mounted on the shared platform and the real distance of infrared ranging sensor from the shared platform to the floor in both static and vertical jumping motion are measured. MATLAB&Simulink model including CPG networks is designed to evaluate the performance of infrared ranging sensor by converting the measurement data from infrared ranging sensor from Voltage to Distance by using function blocks. As the result, the jumping height for each hopping motion can be observed. In addition, the maximum height of the developed tripod hopping robot is also evaluated in order to identify the highest jumping capability. Therefore, MATLAB&Simulink model with maximum height detector system is designed without including the PI controller system. As the result, the effectiveness of the maximum height detector system for the developed tripod hopping robot is confirmed in order to evaluate the highest and stable jumping height.